The market in weapons and Cosa nostra. The alarm raised by Falcone (Rivista di Studi e Ricerche sulla criminalità organizzata, 2018)
The section “History and memory offers the text of the speech entitled “organized crime and arms” that was held by Giovanni Falcone in 1984 in Brescia. In that occasion the judge highlighted the relation between organized crime and financial crime. He underlined the relation between arms trafficking, drug trafficking and illicit financial flows, giving explanation of the close connection between mafia and arms.Keywords: Falcone, Brescia, 1984, organized crime, arms